2005
DOI: 10.1381/0960892053576839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Lipid Profile after Bilio-intestinal Bypass and Gastric Banding in Patients with Morbid Obesity

Abstract: The BI-bypass but not the AGB leads to a persistent and marked beneficial effect on blood LDL cholesterol associated with an increased cholesterol fecal output. BI-bypass but not AGB is indicated in morbidly obese patients with hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…These levels did not increase until the sixth month PS, but this increase did not become significant. Contrary to the other groups [14,37], HDL-c values in non-DM were all over 35 mg/dL at the end of the study, except 7% of patients that show PS HDL-c levels lower than reference values (35 mg/ dL). Our results agree with the meta-analysis of Buchwald et al [42], in which they observed a significant decrease in TC, LDL-c, and TG, but there was no significant increase in HDL-c.…”
Section: Discussioncontrasting
confidence: 57%
“…These levels did not increase until the sixth month PS, but this increase did not become significant. Contrary to the other groups [14,37], HDL-c values in non-DM were all over 35 mg/dL at the end of the study, except 7% of patients that show PS HDL-c levels lower than reference values (35 mg/ dL). Our results agree with the meta-analysis of Buchwald et al [42], in which they observed a significant decrease in TC, LDL-c, and TG, but there was no significant increase in HDL-c.…”
Section: Discussioncontrasting
confidence: 57%
“…These improvements are part of the many beneficial effects of weight loss, and RYGB induced weight loss in particular. The decrease in HDL in our study, although not a beneficial effect of RYGB, has been reported in human studies in the early post-operative state with increases later in recovery [11,12]. Interestingly, the metabolic parameters in SH rats were not significantly different from SC and RYGB-operated rats at time of sacrifice.…”
Section: Discussionsupporting
confidence: 52%
“…In 2 comparative studies with follow-up times up to 3 years, the levels of HDL after bilio-intestinal bypass were lower than the preoperative values. Conversely, the control group that underwent AGB had a significant rise in HDL [77,78].…”
Section: Apolipoproteins A-iv and A-i In Relation To Gi Anatomic Changesmentioning
confidence: 88%